2013
DOI: 10.2478/amma-2013-0026
|View full text |Cite
|
Sign up to set email alerts
|

Study of Cyclodextrin/Fluoroquinolone Inclusion Complexes by Capillary Electrophoresis

Abstract: Introduction:In the present work we evaluated the complexation role of cyclodextrins toward fl uoroquinolones in an attempt to assess their potential as new formulation additives for more effi cient fl uoroquinolone delivery and as selectors in capillary electrophoresis. Material and method: Guest-host interactions of two second generation quinolones, ciprofl oxacin and norfl oxacin with four cyclodextrins, beta-cyclodextrin (-CD), gamma-cyclodextrin (-CD) and two beta-cyclodextrin derivatives, 2-hydroxyprop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Moreover, when M-␤-CD was used as a CS, the complexation constants were higher for 10-hydroxywarfarin than for warfarin, and therefore, the former exerts stronger affinity to M-␤-CD and stronger stereoselective effect. RAMEB was used in CE as a CS for the enantioseparation of several analytes, such as omeprazole, amlodipine, and ofloxacin [51][52][53][54]. Briefly, Hancu et al [51] studied the chiral separation of omeprazole by using several neutral and negatively charged CDs.…”
Section: Neutral CD Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, when M-␤-CD was used as a CS, the complexation constants were higher for 10-hydroxywarfarin than for warfarin, and therefore, the former exerts stronger affinity to M-␤-CD and stronger stereoselective effect. RAMEB was used in CE as a CS for the enantioseparation of several analytes, such as omeprazole, amlodipine, and ofloxacin [51][52][53][54]. Briefly, Hancu et al [51] studied the chiral separation of omeprazole by using several neutral and negatively charged CDs.…”
Section: Neutral CD Derivativesmentioning
confidence: 99%
“…RAMEB was also used for the chiral separation of sibutramine, and the method was validated based on linearity, precision, LOD, LOQ, and intra‐ and interday reproducibility . In a recent study , molecular modeling demonstrated that RAMEB interacts with ofloxacin enantiomers mainly by Van der Waals forces, and a small difference in the binding energies of the two enantiomers was observed. IR results indicated that a part of the oxazine ring is embedded in the CD cavity.…”
Section: Chiral Selectorsmentioning
confidence: 99%